Local scale extreme low pH conditions and genetic differences shape phenotypic variation in a broad dispersal copepod species - Aguilera, Victor M.; Sepulveda, Fabiola; von Dassow, Peter; Gaitán-Espitia, Juan Diego; Mesas, Andrés; Vargas, Cristian A. (Frontiers in Marine Science, 2023)
Extreme low pH events in estuaries and upwelling areas can modulate the phenotypic and genetic diversity of natural populations. To test this hypothesis, we explored the linkage between local scale extreme low pH events, genetic diversity, and variation in fecundity-related traits (body size, egg size, and egg production rate) in the broad-dispersal copepod Acartia tonsa. We assessed genetic and phenotypic characteristics of populations by contrasting extreme low pH environments (upwelling and temperate estuary) in the coastal Southeast Pacific, under natural and experimental conditions. These populations showed significant genetic differentiation with higher diversity in mitochondrial and nuclear loci (encoding mtCOI and 18S rRNA) in the estuarine population. Copepods from this population are exposed to more frequent extreme low pH events (< 7.7), and the adult females exhibit consistent phenotypic variation in body size, egg size, and egg production rate across different cohorts. Experimental acclimation to extreme low pH conditions revealed no significant differences in fecundity-related traits between A. tonsa populations. Although these results partially support our hypothesis, the experimental findings suggest other drivers might also influence phenotypic differences in the local environments.